The use of a geographical information system (GIS) to evaluate the distribution of tuberculosis in a high-incidence community - BEYERS, N; GIE, R. P; ZIETSMAN, H. L; KUNNEKE, M; HAUMAN, J; TATLEY, M; DONALD, P. R (South African medical journal, 1996)
To determine the geographical distribution of tuberculosis in the two Western Cape suburbs with the highest reported incidence of tuberculosis. Descriptive illustrative study. Two adjacent Western Cape suburbs covering 2.42 km2 with a population of 34,294 and a reported tuberculosis incidence of > 1,000/100,000. All patients notified as having tuberculosis over a 10-year period (1985-1994). None The geographical distribution of the cases was determined using a geographical information system (GIS) and the National Population Census (1991). One thousand eight hundred and thirty-five of the 5,345 dwelling units (34.3%) housed at least 1 case of tuberculosis during the past decade and in 483 houses 3 or more cases occurred. These cases were distributed unevenly through the community, with the tuberculosis incidence per enumerator subdistrict (ESD) varying from 78 to 3,150/100,000 population. In a small area with a high incidence of tuberculosis, the cases are spread unevenly through the community and there are certain houses where tuberculosis occurs repeatedly. This information should be used to direct health services to concentrate on certain high-risk areas.